Photo-oxidative action in cervix carcinoma cells induced by HpD — mediated photodynamic therapy - Saczko, J.; Skrzypek, W.; Chwilkowska, A.; Choromanska, A.; Pola, A.; Gamian, A.; Kulbacka, J. (Experimental Oncology, 2009)
Photodynamic therapy leads to oxidative stress through the generation of free radicals. Oxidative stress causes damage to cellular macromolecules such as nucleic acids, proteins and lipids. Aim: To examine the hematoporphyrin derivative (HpD) — mediated photodynamic effect on cervical adenocarcinoma cell line HeLa. Methods: The HpD localization in HeLa cells was analyzed by confocal microscopy with epi-fluorescence system. Lipid peroxidation (LPO) was estimated by measurement of the concentration of malondialdehyde, protein degradation — by modified Ellman’s method, superoxide dysmutase (SOD) — using Ransod Kit. The expression of inducible nitric oxide synthase (iNOS) was detected by immunocytochemical staining. Results: The HpD was distributed all over the cytoplasm with preferential localization in the inner side of the plasma membrane and around the nuclear envelope. The process of photosensitizer distribution was time dependent. PDT-HpD increased the level of malonodialdehyde (MDA), SOD activity and the expression of iNOS in HeLa cells. However, PDT induced the decrease in the level of protein-associated thiol groups. Conclusions: Our study showed the important role of PDT-mediated oxidative stress in HeLa cells. HpD-PDT might be alternative and less invasive approach for treatment of patients with cervical cancer resistant for standard chemotherapy and radiotherapy.